2017
DOI: 10.1039/c7ta05841a
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-temperature solid oxide electrolysis cells with thin proton-conducting electrolyte and a robust air electrode

Abstract: A proton-conducting solid oxide electrolysis cell (H-SOEC) is a promising device that efficiently converts electrical energy to chemical energy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(43 citation statements)
references
References 49 publications
0
43
0
Order By: Relevance
“…Figure c compares the electrolysis performance of our optimized cells with those of oxygen‐conducting SOECs reported in the literature . Some recent advances of electrolysis cells based on proton conductors (such as ) are not shown here, as the operating temperatures (400–600 °C) and steam contents (up to 10 vol%) reported for these proton‐conducting SOECs are very different from the ones based on conventional oxygen conductors (700–900 °C, 50 vol% or higher steam content). The cell with Pr 6 O 11 ‐SDC oxygen electrode achieved very high electrolysis performance, surpassing conventional electrode‐supported cells and all previous metal‐supported electrolysis cells.…”
Section: Resultsmentioning
confidence: 90%
“…Figure c compares the electrolysis performance of our optimized cells with those of oxygen‐conducting SOECs reported in the literature . Some recent advances of electrolysis cells based on proton conductors (such as ) are not shown here, as the operating temperatures (400–600 °C) and steam contents (up to 10 vol%) reported for these proton‐conducting SOECs are very different from the ones based on conventional oxygen conductors (700–900 °C, 50 vol% or higher steam content). The cell with Pr 6 O 11 ‐SDC oxygen electrode achieved very high electrolysis performance, surpassing conventional electrode‐supported cells and all previous metal‐supported electrolysis cells.…”
Section: Resultsmentioning
confidence: 90%
“…Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive. Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive.…”
Section: Currentfabrication Methods Of Anode-supported Cells and Perspmentioning
confidence: 99%
“…Currently,t he mostc ommons tructure for BZY20 electrolytebased cells is an anode-supported one, which is composed of at hick anode layer and at hin electrolyte layer,c oupled with a co-sintering process and an optionals intering additive, which allowst he implementation of electrolyte layers thinned to tens of micrometers with minimized loss of ohmic resistance. Not only fuel cells, but other electrochemical devices,i ncluding electrolyzers, [53,54] hydrogen separation [55,56] and methane reforming materials, [57,58] have been fabricated by such a method.H owever,a sc larified in our preliminary experiment (Figure 1), regardless of whether sintering additives were added on purpose or not, NiO in the anode diffused into the electrolyte layer and played the role of the sintering additive. Al iterature review revealed that the co-sintered cells have a conductivity of approximately 0.001-0.003Scm À1 (Table1), in accordance with the resultsi nt his work;t hat is, the BZY20 sample dopedw ith 1o r2wt %N iO had ac onductivity (mainly proton conduction) lower than 0.004 Scm À1 in wet hydrogen (Figure 9).…”
Section: Currentfabrication Methods Of Anode-supported Cells and Perspmentioning
confidence: 99%
“…And currently, Y-doped BaZrO3 (BZY) receives the most interest, due to its high proton conductivity (> 0.01 Scm -1 at 450 o C for BaZr0.8Y0.2O3δ [7,8]) and significant chemical stability against carbon dioxide and water vapor [9,10]. Potential to implement the BZY electrolyte into fuel cells [11][12][13][14] and electrolysis cells [15,16] has been verified on bottom cells in a lab scale. However, reviewing the literature, these BZY electrolyte is almost limited to three compositions; BaZr0.9Y0.1O3-δ (BZY10) [15,17], BaZr0.85Y0.15O3-δ (BZY15) [14,18] and BaZr0.8Y0.2O3-δ (BZY20) [11-13, 16, 19-22].…”
Section: Introductionmentioning
confidence: 99%